The Influence of Education Level, Accounting Understanding, and Business Size on The Preparation of Financial Reports of Micro, Small, and Medium Enterprises Based on Financial Accounting Standards for Micro, Small, and Medium Entities - Pratiwi, Nabilah Hasyyati Winda; Pabulo, Azfa Mutiara Ahmad (SIMAK, 2024)
MSMEs play a very important role in helping the economy in Indonesia. For every ongoing business​ walk, No will let go from recording report finance. Research objectives for knowing the variables in influence compilation report MSME finances according to EMKM SAK which includes level of education, understanding accounting, and measurement business. Methodology study This method is quantitative. Research results using hypothesis testing show that Education level, understanding of accounting, and measurement of business influence compilation report MSME finance based on SAK EMKM. Increasing education levels tall will make perpetrator business to compose report correct finances. The more Lots understanding of accounting, the more good use of SAK EMKM. In addition, the more the magnitude of the business so must more thorough in do recording information.